Remarks to G20 Leaders’ Virtual Summit - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass explained the World Bank Group's work to take broad swift action to respond to the coronavirus pandemic. He spoke about finalizing an additional package that will focus on the broader economic consequences. He was concerned about the poor and densely populated countries like India and how the Bank is working hard to provide support through Bank's public and private sector tools. He highlighted the role of private sector support which is critical. He mentioned the Bank working closely with the IMF and WHO, among others, to determine needs assessments of client countries. He also highlighted the importance of addressing debt vulnerabilities as this crisis will hit hardest poor countries that have high levels of indebtedness. He spoke about how the Bank urged many of the G20 leaders and other official bilateral creditors to suspend debt payments due from IDA countries, effective immediately to determine what kind of debt relief or restructuring is needed. He concluded by saying that the World Bank Group and the IMF are working quickly to flesh out an approach for debt relief for poorer countries.